Addressing Persistent False Lumen Flow in Chronic Aortic Dissection: The Knickerbocker Technique. (February 2014) - Kölbel, Tilo; Carpenter, Sebastian W.; Lohrenz, Christina; Tsilimparis, Nikolaos; Larena-Avellaneda, Axel; Debus, Eike Sebastian
Purpose: To describe an innovative technique to occlude distal backflow into a false lumen aneurysm by controlled rupture of the dissection membrane after stent-graft implantation. Technique: The "Knickerbocker technique" involves relining the true lumen in the descending aorta with an oversized thoracic tubular endograft, followed by controlled rupture of the dissection membrane using a large compliant balloon within the graft's midsection. This maneuver, which allows expansion of the stent-graft's midsection into the false lumen, was developed in order to occlude the large false lumen distally and thus prevent continued false lumen perfusion through distal abdominal entry tears. The technique has been successfully used in 3 patients with ruptured or symptomatic chronic false lumen aneurysm in type B aortic dissection. There was no short-term mortality associated with the procedure. After a mean follow-up of 8 months, the false lumen aneurysm remained thrombosed, with no mortality after a mean clinical follow-up of 22 months. Conclusion: The Knickerbocker technique appears to be feasible and effective in inducing false lumen thrombosis in selected patients who undergo stent-grafting for chronic type B aortic dissection.